Communication Development Practice of Sound and Rhythm Perception at SLB YRTRW Surakarta - Wan Zhaliha; Sunardi, Sunardi; Joko Yuwono (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
The ability to detect sounds in deaf children often experiences obstacles, due to obstacles to the auditory senses. To improve the ability to detect sounds in deaf children, a sound and rhythm perception communication development (PKPBI) learning program is needed. This research aims to describe the procedures, methods, and tools used in PKPBI learning, as well as the challenges faced by teachers in implementing the learning. The subjects in this study were PKPBI subject teachers and four grade X students at SLB YRTRW Surakarta. This research used qualitative methods in the form of semi-structured interviews and observations. The results showed that the implementation of PKPBI learning at each stage has different procedures, methods, and tools. The challenges experienced at these four stages include the low level of children's attention, the degree of residual hearing that children have, and inadequate facilities and infrastructure.